Emotions and social relations - Burkitt, Ian (London SAGE, 2014)
"This book is a compelling and timely addition to the study of emotions, arguing that emotion is a response to the way in which people are embedded in patterns of relationship, both to others and to significant social and political events or situations. Going beyond the traditional discursive understanding of emotions, Burkitt investigates emotions as a complex and dynamic phenomenon that includes the whole self, body and mind, but which always occur in relation to others." -- From the back cover.
Includes bibliographical references (pages [173]-183) and index.
Keywords: Social psychology; Emotions -- Sociological aspects